2003
DOI: 10.1002/jmv.10348
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response after RSV infection in children younger than 1 year of age living in a rural area of Mozambique

Abstract: Serological responses have been studied in respiratory syncytial virus (RSV) infected children < 1 year of age attending the outpatient department of the Manhiça District Hospital (Mozambique). Molecular characterization of viral RNA in nasopharyngeal aspirates from the infected children indicated a high level of genetic uniformity among the infecting viruses, all of which belonged to a single genotype of RSV group A. A representative virus strain, Moz00, was isolated from one of the infants and was used, toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
1
9
1
1
Order By: Relevance
“…19 In this study, viral type, viral load, and duration of shedding did not influence the antibody response. The finding of a lack of a correlation between viral type and antibody response is in disagreement with the data reported by Roca et al 15 These authors found that although an immune response after RSV infection was evidenced in all children regardless of the viral type, different RSV strains could evoke different immune responses in patients infected by RSV A, who showed the highest increments in antibody titres. In our study population, no statistically significant difference in GMT was found between children infected by RSV type A and those affected by RSV type B, although GMT fold changes were higher in RSV-A cases.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…19 In this study, viral type, viral load, and duration of shedding did not influence the antibody response. The finding of a lack of a correlation between viral type and antibody response is in disagreement with the data reported by Roca et al 15 These authors found that although an immune response after RSV infection was evidenced in all children regardless of the viral type, different RSV strains could evoke different immune responses in patients infected by RSV A, who showed the highest increments in antibody titres. In our study population, no statistically significant difference in GMT was found between children infected by RSV type A and those affected by RSV type B, although GMT fold changes were higher in RSV-A cases.…”
Section: Discussioncontrasting
confidence: 84%
“…On the other hand, all the other studies regarding specific antibody production in children infected by RSV showed results quite similar to those reported in our study. [10][11][12][13][14][15][16] Moreover, similar results were recently confirmed by Sande et al, 18 who reported that in comparison to the mean acute phase antibody titer, the mean convalescent titer was lower in the 0-1.9 month age class, no different in the 2-3.9 month age class and greater in all age classes 4 months.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…One infant in this study who was experiencing a second documented RSV infection within the first few months of life still lacked mutations in RSV-specific gene segments. These data strongly suggest that inefficiencies in the molecular and cellular mechanisms controlling somatic hypermutation may underlie poor infant antibody responses to vaccines and viral infections (Brandenburg et al, 1997; Murphy et al, 1986a; Murphy et al, 1986b; Roca et al, 2003). Zemlin et al analyzed global Ig repertoire and discovered that preterm infants exhibited reduced somatic mutations compared with term infants (Zemlin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have documented the poor humoral immune response of infants to respiratory syncytial virus (RSV) and other pathogens that commonly cause infection early in life (Brandenburg et al, 1997; Murphy et al, 1986a; Murphy et al, 1986b; Roca et al, 2003). Passively-acquired maternal antibodies suppress the primary antibody response in infants.…”
Section: Introductionmentioning
confidence: 99%